Comparative analysis of the physicochemical properties and antioxidant activities of organic Riceberry rice from different growing locations. - Charoenjit, K.; Huaisan, K.; Wanyo, P. (International Journal of Agricultural Technology, 2025)
The study revealed significant variations in the physicochemical and antioxidant properties of organic Riceberry rice cultivated in four districts of Kalasin, Thailand. Rice from Site 4 (Kham Muang) showed the highest antioxidant activities, with elevated values in DPPH radical scavenging (923.17 µg Trolox/g), FRAP (1001.39 µg FeSO₄/g), total phenolic content (816.26 µg GAE/g), and total anthocyanin content (51.86 g c3g/100g), indicating favorable conditions for phenolic compound biosynthesis. Conversely, rice from Site 3 (Khong Chai) had the highest amylose content (14.20%), resulting in lower peak viscosity and greater setback viscosity, which suggests increased starch retrogradation and firmer rice texture. Site 1 (Mueang) rice displayed the highest onset and peak gelatinization temperatures, indicating a more stable starch structure, while Site 4 had the highest peak viscosity (189.58 RVU) and breakdown, reflecting a starch with greater water absorption and gel-forming capacity. These variations are linked to differentiate in soil texture, drainage, and environmental factors, which affected the rice’s nutrient uptake, antioxidant activity, and starch properties.